Customary Marriage vs. Human Rights: Legal Challenges of Kawin Tangkap in Sumba, Indonesia - Firman Laia (CV. Era Digital Nusantara, 2025)
Abstract: Marriage, as a social and legal institution, reflects the cultural values of a society. In Sumba, the practice of kawin tangkap (forced marriage by abduction) persists despite legal and human rights concerns. This practice, in which a man